Tumors and the immune system – reciprocal interaction - Florek, Julia; Miczek, Marcin; Dębska, Patrycja; Groele, Adrian; Śmiałek, Sara; Guzik, Natalia; Jaklik, Dominik; Cholewa, Dominika; Starzyk, Radosław; Słaby, Wiktor (Quality in Sport, 2025)
Background. Tumor formation is a multi-stage process influenced by the complex reciprocal interaction between cancer cells and the host's immune system. This relationship is described by the concept of immunoediting, consisting of elimination, equilibrium, and escape phases. Paradoxically, while the immune system can destroy cancer cells, chronic inflammation and immunosuppressive mechanisms (e.g., Treg activity, myeloid-derived suppressor cells) can promote tumorigenesis and metastasis. Aim. The aim of this study is to review current knowledge regarding the mechanisms of immune evasion by tumors and to evaluate the efficacy of various immunotherapy strategies, including active, passive, adoptive, and combination therapies. Material and methods. A comprehensive review of scientific literature was conducted using PubMed, Scopus, and Google Scholar databases. The analysis included original and review articles published primarily between 2000 and 2025, focusing on keywords such as carcinogenesis, tumor immunoediting, checkpoint inhibitors, and combination therapy. Results. The immune system plays a dual role in cancer development. Tumor cells employ mechanisms like MHC class I downregulation and expression of checkpoint molecules (PD-L1, CTLA-4) to evade immune surveillance. Modern immunotherapy, particularly checkpoint inhibitors (e.g., nivolumab, pembrolizumab) and adoptive cell transfer (CAR-T), has revolutionized oncology. Recent data also highlight the potential of combination therapies—pairing immunotherapy with chemotherapy, radiotherapy, or targeted therapy—to overcome resistance. Furthermore, the gut microbiota has emerged as a crucial factor modulating the response to immunotherapy. Conclusions. Immunotherapy represents a pillar of modern oncology. However, the heterogeneity of tumor microenvironments necessitates personalized approaches.